The relationship between culture and perception of ethical problems in international Marketing - Armstrong, Robert W. (Journal of business ethics, 1996)
This research study sought to identify whether there is a relationship between ethical perceptions and culture. An examination of the cultural variables suggests that there is a relationship between two of Hofstede's cultural dimensions (i.e., Uncertainty Avoidance and Individualism) and ethical perceptions. This finding supports the hypothetical linkage between the cultural environment and the perceived ethical problem variables posited in Hunt and Vitell's General Theory of Marketing Ethics (1986).